Ostasien. Hirse – Wann das erste Getreide im nördlichen Ostasien domestiziert und verbreitet wurde. Die Arbeiten des Jahres 2019 (Projekte „BAYCHRON“ und „Bridging Eurasia“) - Wagner, Mayke; Leipe, Christian; Long, Tengwen; Sergusheva, Elena A.; Tarasov, Pavel E. (e-Forschungsberichte des DAI, 2020)
Although broomcorn and foxtail millet are among the earliest staple crop domesticates, their spread and impacts on demography remain controversial, mainly because of the use of indirect evidence. Bayesian modelling applied to a dataset of new radiocarbon dates derived from domesticated millet grains suggests that after their initial cultivation in the crescent around the Bohai Sea ca. 5800 cal yr BC (median date), the crops spread discontinuously across eastern Asia. In northern China, millet-based agriculture expanded westward only with a delay of ca. 1000 years between neighbouring regions, but supported a quasi-exponential population growth from 6000 to 2000 cal yr BC. Domesticated millet reached Kazakhstan ca. 2300 cal yr BC from where it was brought East again and introduced to Xinjiang together with wheat, barley, sheep/goat and cattle ca. 1900 cal yr BC. Even the Korean peninsula is relatively near to the area of millet’s initial domestication, its cultivation there did not start until ca. 3700 cal yr BC, i.e. after a time lag of about 2000 years. From Korea millet was taken to Japan ca. 1000 cal yr BC by peasants who kicked-off millet and rice agriculture at the easternmost isles of the Eurasian continent.